Evaluation of a volume of fluid CFD methodology for the oil film thickness estimation in an aero-engine bearing chamber - Bristot, Andrea; Morvan, Herve; Simmons, Kathy (2016)
The presented work aims to identify a Volume of Fluid (VOF) CFD approach for the transient simulation of air/oil flows inside an aero-engine bearing chamber. Typically VOF requires relatively fine grids and consequently small time-steps to sufficiently resolve the formation of oil films and their interaction with air flows. The need to achieve a stationary-state which requires flow times on the order of seconds makes the compromise between simulation accuracy and simulation times a challenging choice when using the VOF method. In this work, the use of the Compressive Interface Reconstruction scheme with bounded second order implicit time discretization has enabled a significant speed-up of the simulation times against the previously adopted explicit Geometric-Reconstruction scheme. The results are evaluated against experimental data available in the literature.